2022
DOI: 10.1021/acsabm.1c01322
|View full text |Cite
|
Sign up to set email alerts
|

Unscrambling the Influence of Sodium Cation on the Structure, Bioactivity, and Erythrocyte Compatibility of 45S5 Bioactive Glass

Abstract: The 45S5 bioglass uttering Class A bioactivity promotes both osteoconduction as well as osteoinduction. Though one of the higher reactive bioactive materials known with structural and physiological influence upon ionic modulation, poor mechanical properties are perceived. The possible solution to overcome the weak stability is to choose material's composition that provides retained bioactivity and improved mechanical stability. Meanwhile, primary burst out of Na + ions increases the local pH, harms cell life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…It is observed that micro‐hardness decreased from CP1 to CP3 gradually and enhanced for CP4. Generally, the value of Vicker's hardness is defined as the quotient of test load F and the surface area of the indentation and is given by the formula, 37,48 HV=0.102FA=0.1891Fd2 The hardness gradually decreased with respect to the sintering temperature, which is correlated with BET results (Figure 7C) upto 900°C. This is because, from Equation (5), it is clear that if surface area increases, micro‐hardness value decreases.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is observed that micro‐hardness decreased from CP1 to CP3 gradually and enhanced for CP4. Generally, the value of Vicker's hardness is defined as the quotient of test load F and the surface area of the indentation and is given by the formula, 37,48 HV=0.102FA=0.1891Fd2 The hardness gradually decreased with respect to the sintering temperature, which is correlated with BET results (Figure 7C) upto 900°C. This is because, from Equation (5), it is clear that if surface area increases, micro‐hardness value decreases.…”
Section: Resultsmentioning
confidence: 53%
“…It is observed that micro-hardness decreased from CP1 to CP3 gradually and enhanced for CP4. Generally, the value of Vicker's hardness is defined as the quotient of test load F and the surface area of the indentation and is given by the formula, 37,48 HV ¼…”
Section: Micro Vickers Hardness Analysismentioning
confidence: 99%
“…This symbolizes the larger precipitation of the hydroxyl carbonate apatite (HCA) layer on the surface; i.e., if the mass of the molecule increases, wavenumber shift decreases. 16 To support this finding, −OH band also deepens in intensity in the E-Si-P biomaterial. Hence, it can be concluded that E-Si-P shows a larger amount of HCA precipitation on immersion in SBF than E-Si and Si-E.…”
Section: Ftir Spectroscopic Functional Group Analysismentioning
confidence: 83%
“…Briefly, the value of HV was multiplied by 9.807 to yield the values in MPa. 16 2.8. Protein Adsorption Study.…”
Section: Vickers Hardness Testmentioning
confidence: 99%
See 1 more Smart Citation